Da Isacco a Giobbe nel percorso teatrale di Ħanoch Levin (Altre Modernità, 2011)
The article examines two plays, in them the Israeli dramatist Ħanok Levin deals with biblical subjects. The first is the sketch “The Binding of Isaac”, that was performed in 1970, inside the satyrical cabaret “The Queen of the Bathroom”. The second is “Job’s Sorrows”, one of the most important of Levin’s ‘mythological dramas’, that was performed in 1981, under the production of the autor himself. Through the sketch - and the song that completes it - Levin criticizes the Israelis euforia after the Six Days war, while in the drama he starts from “Job’s Book” to ask fundamental questions about human life, such as the significance of  sorrow and ‘what is the human being’. In Levin’s drama Job’s figure blends into Christ’s figure, and in this way the dramatist deals also with the proposal of christian Redemption, which he refuses too. In the last part of the play, the focus moves to the relation between pleasure and sorrow, and to the spectacularisation of both in the ‘show’s society’: the crucifized Job becomes the principal attraction of a circus and his agony moans get confused with the pleasure moans of a striptease. In this part Levin asks also the metatheatrical question about what one has to expect from the performance. Is clear answer is that there is nothing behind the performance, so as nothing is behind the sorrow, but the strenght with these questions return in his tragical dramas disclose that such problems were for him both a worry and a source of poetry.